Toy story 3 [videorecording (DVD)] - Unkrich, Lee; Hanks, Tom; Allen, Tim, 1953-; Cusack, Joan, 1962-; Rickles, Don; Ratzenberger, John; Keaton, Michael, 1951-; Dalton, Timothy, 1944-; Beatty, Ned; Shawn, Wallace (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
As Andy prepares to leave for college, his loyal toys find they have been donated to the Sunnyside Daycare where untamed tots with their sticky little fingers do not play nice. So, it's all for one and one for all as they join Barbie's counterpart Ken, a thespian hedgehog named Mr. Pricklepants, and a pink, strawberry-scented teddy bear called Lots-o'-Huggin' Bear to plan their great escape and ensure that no toy gets left behind.